Enteromegaly and cardiomegaly in Chagas disease. Issue 4 (December 1963) - Köberle, Fritz
Abstract : Chagas disease due to a trypanosome infection may lead to extensive destruction of ganglion cells in the peripheral autonomic system and may result in gross enlargement of the oesophagus, colon, and heart. From studies on nerve cell counts it is concluded that the number of ganglion cells in the oesophagus must be reduced to less than half to produce functional disturbances in the oesophagus and to one tenth to produce a megaoesophagus. Problems of terminology are discussed.